Synthesis and Characterization of Several New Homopolymers, Copolymers and Phenolic Resins of N-Substituted Citraconisoimides - Al-Azzawi, Ahlam; Yaseen, Mustafa (Iraqi Journal of Science, 2023)
Four N-substituted citraconisoimides were prepared via dehydration of the corresponding prepared citraconamic acids using N,N\-dicyclohexylcarbodiimide as dehydrating agent. The prepared citraconisoimides were introduced in free radical homopolymerization producing four new poly citraconisoimides. Also the prepared citraconisoimides were introduced in free radical copolymerization with three vinylic monomers including acrylonitrile, methylmethacrylate and methylacrylate producing new copolymers having different physical properties. Moreover two new phenolic resins containing pendent citraconisoimide moiety were prepared via condensation polymerization of N-(hydroxyphenol)citraconisoimide with formaldehyde. The new homopolymers and copolymers are of great importance since they contain isoimide ring in their repeating units which exhibit better processing properties and can rearrange gradually with time and use to the more stable structure of the corresponding imides having thermosetting properties.